2020
DOI: 10.1002/cptc.202000134
|View full text |Cite
|
Sign up to set email alerts
|

Unsymmetrical 2,4,6‐Triarylpyridines as Versatile Scaffolds for Deep‐Blue and Dual‐Emission Fluorophores

Abstract: Pyridines substituted with different aromatic groups at C-2, C-4 and C-6 were prepared following a Kröhnke synthetic route. Introducing ortho-anisole at C-2 resulted in deep blue emitters in solution, with quantum yields up to 74 %. On the other hand, when ortho-phenol was introduced, forming a strong hydrogen bond with the pyridine nitrogen, excited-state intramolecular proton transfer was witnessed by the dual emission of the fluorophores, which is sensitive to the dye environment. The phenyl ring at C-4 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Once again, using the methyl ( E )-2-(4-methoxybenzylidene)betulonate ( 3b ) as starting material, the reaction was performed in the presence of an excess of the Kröhnke salt 7 and ammonium acetate, in refluxing acetic acid for 24 h. Compound 8 was obtained in poor yield (25%), still recovering some starting material 3b . In the literature, for simpler triarylpyridine derivatives, prepared through a similar methodology, it was observed that the presence of strong electron-donating groups, such as dimethylamino or methoxy groups, did not favor the reaction, since the corresponding triarylpyridines were obtained in poor yields (24–37%) [ 28 ]. Therefore, this might have happened for the diarylpyridine-fused BoOMe compound 8 , as the starting material 3b also possesses a strong electron-donating methoxy substituent.…”
Section: Resultsmentioning
confidence: 99%
“…Once again, using the methyl ( E )-2-(4-methoxybenzylidene)betulonate ( 3b ) as starting material, the reaction was performed in the presence of an excess of the Kröhnke salt 7 and ammonium acetate, in refluxing acetic acid for 24 h. Compound 8 was obtained in poor yield (25%), still recovering some starting material 3b . In the literature, for simpler triarylpyridine derivatives, prepared through a similar methodology, it was observed that the presence of strong electron-donating groups, such as dimethylamino or methoxy groups, did not favor the reaction, since the corresponding triarylpyridines were obtained in poor yields (24–37%) [ 28 ]. Therefore, this might have happened for the diarylpyridine-fused BoOMe compound 8 , as the starting material 3b also possesses a strong electron-donating methoxy substituent.…”
Section: Resultsmentioning
confidence: 99%
“…All compounds are fluorescent in DMSO solution and show large Stokes’ shifts of ca. 125 nm, characteristic of fluorophores presenting ESIPT [ 43 , 45 , 46 ]. The maximum emission wavelength of 7b – d is also slightly red shifted (5–10 nm) moving down the halogen series ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the example of Figure 8, the relative minimum of the excited state directly demonstrated the transfer of the proton from the phenol to the pyridine. [51] However, this is not always the case, due to inadequate calculation parameters or system definition. Alternatively, one can propose an excited-state geometry and vary the parameters such as bond length or angle torsion.…”
Section: Computer-assisted Decoding Esptmentioning
confidence: 99%